On the influence of vertical ground movements on Late-Quaternary sea-level records. A comprehensive assessment along the mid-Tyrrhenian coast of Italy (Mediterranean Sea). (1st March 2022) - Mattei, Gaia; Caporizzo, Claudia; Corrado, Giuseppe; Vacchi, Matteo; Stocchi, Paolo; Pappone, Gerardo; Schiattarella, Marcello; Aucelli, Pietro P.C.
Abstract: The mid-Tyrrhenian coast is the most complex volcano-tectonic sector in the Mediterranean basin. Here the vertical ground movements (VGMs) due to the interaction between extensive tectonic processes and volcano-tectonic activities have a significant impact on both past and future sea-level evolution. This area represents the youngest basin of the western Mediterranean and it hosts one of the most active volcanic districts, formed by the Campi Flegrei and Vesuvius volcanoes, which are worldwide known for the vertical ground movements accompanying their volcanic activity since the Late Pleistocene. The short-lived alternation of subsidence and uplift has induced great changes in inland areas and abrupt coastal landscape transformations since that time. This study aimed to spatially constrain the magnitude of the vertical displacements which significantly affected this coastal sector during the last millennia. We then reconstructed the multiple relative sea-level oscillations that occurred during the Late-Quaternary by developing a comprehensive WebGIS of sea-level index and limiting points (https://dist.altervista.org/seaproxy/ ). This includes newly produced sea-level data from recent marine surveys, which were coupled to previously available data standardized according to the recent international guidelines for RSL studies. This allowed producing a multiproxy dataset composed of depositional, erosional, biological, and archaeological sea-level markers, in this very complex Mediterranean area. The collected sea-level data were further compared with a number of geophysical predictions in order to disentangle the different components which influenced the sea-level evolution. Moreover, the tectonic rates derived from the available MIS 5e sea-level data were used to shift the LIG elevations vertically and backwards in time in order to constrain the Last Interglacial RSLs to certain levels depending on the areas. Finally, we used GIS techniques to spatially constrain the coastal sectors more vulnerable to the coupled effects of future sea-level rise and VGMs in the next decades. Highlights: Reconstruction of Late Quaternary sea-level oscillations in the mid-Thyrrenian area. Development of a WebGIS of sea-level data in the mid-Thyrrenian area. Definition of Vertical ground movements due to volcano-tectonic activities. Holocene vertical displacements by comparing sea-level data and GIA models. Long-term tectonic rates from MIS 5e sea-level data.